PEMANFAATAN MEDIA DIGITAL DALAM PENGEMBANGAN DESA WISATA DI DESA BURAI KABUPATEN OGAN ILIR SUMATERA SELATAN - Huspita sari, Feni (Lentera Ilmu Madani, 2024)
Burai Village, which is located in Ogan Ilir Regency, South Sumatra Province, with an area of around 2.66 square kilometers, is one of the tourism villages that is starting to be developed by the Ogan Ilir Regency government. In an increasingly advanced era, digital media cannot be separated from almost all community activities, one of which is developing tourism in Burai village. This article explains the Community Service activities of the Annisa Dwi Salfaritzi College of Administration and Government Palembang in Burai Village with the theme